Differences in cardiorespiratory responses of young and senior male endurance athletes to maximal graded exercise test - Michalis, M.; Finn, K. J.; Podstawski, R.; Gabnai, S.; Koller, A.; Cziráki, A.; Szántó, M.; Alföldi, Z.; Ihász, F. (Physiology International, 2020)
Within recent years the popularity of sportive activities amongst older people, particularly competitive activities within certain age groups has increased. The purpose of this study was to assess the differences in the cardiorespiratory output at anaerobic threshold and at maximal power, output during an incremental exercise, among senior and young athletes. Ten elderly male subjects [mean (SD) age: 68.45 ± 9.32 years] and eight young male subjects [mean (SD) age: 25.87 ± 5.87 years] performed an incremental exercise test on a treadmill ergometer. No significant differences in body size were evident; however, the differences between the groups for peak power (451.62 ± 49 vs. 172.4 ± 32.2 W), aerobic capacity (57.97 ± 7.5 vs. 40.36 ± 8.6 mL kg-1 min-1), maximal heart rate (190.87 ± 9.2 vs. 158.5 ± 9.1 beats min-1), peak blood lactate (11 ± 1.7 vs. 7.3 ± 1.4 mmol L-1), and % VO2max at ventilatory thresholds (93.18 ± 4.3 vs. 79.29 ± 9.9%) were significantly lower in the senior athletes. The power output at anaerobic threshold was also higher (392 ± 48 vs. 151 ± 23 W) in the young athletes, explaining the significant difference in terms of performance between these groups. We have observed an evident deterioration in some of the cardiovascular parameters; however, the submaximal exercise economy seems to be preserved with aging. Exercise economy (i.e. metabolic cost of sustained submaximal exercise) was not different considerably with age in endurance-trained adults.